Perkembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Gambar untuk Meningkatkan Keterampilan Generic Sains - Hasanah, Nurdina; Harahap, Siti Aisyah; Nabila, Hanny; Elza, Nanda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to determine the influence of using picture-based worksheets on the learning process material. It is a research and development study. The goal is to understand the process of using worksheets to improve students' critical thinking skills. This research method is used to create a specific product and test its effectiveness. The study aims to develop a product in the form of Student Activity Sheets (LKPD), evaluate the attractiveness of picture-based LKPD, and assess the effectiveness of LKPD in improving student learning outcomes.